Secure authentication approach using Diffie-Hellman key exchange algorithm for WSN. (2016) - Kumar, Sanjay; Singh, R.K.
Most of the sensor network applications are deployed in a hostile environment. So to keep the confidentiality of the information over sensor network, secure communication between the sink and the sensor nodes is required. Cryptographic key distribution provides a solution for this security challenge. This paper presents a secure key distribution using Diffie-Hellman key exchange algorithm and key pre-distribution scheme. It also proposes the design of a tampering alarm to isolate the compromised node in the network after attack. This paper aims at increasing the sensor network security by increasing sensor node's security against tampering and key compromisation, by using hardware tampering module.